Microbially induced carbonate precipitation for wind erosion control of desert soil: Field-scale tests - Meng, Hao; Gao, Yufeng; He, Jia; Qi, Yongshuai; Hang, Lei (Geoderma, 2021)
•Field trials on the use of MICP for wind erosion control of desert soil are conducted.•Soil crusts on loose cohesionless desert soil exist after MICP treatment.•MICP shows pleasurable ecological compatibility and long-term sustainability.•MICP is a promising candidate to mitigate wind erosion of desert soils in drylands. This study examined the potential of microbially induced carbonate precipitation (MICP) in reducing wind erosion of desert soil. Field tests were conducted on artificial mounds and bare sandy land located in Ulan Buh Desert, Ningxia Hui Autonomous Region, China. Results showed that the MICP method could significantly enhance the bearing capacity and wind erosion resistance of the surficial soil through the formation of soil crusts. The optimal cementation solution (containing equimolar urea and calcium chloride) concentration and spraying volume, were 0.2 M and 4 L/m2, respectively. Under this condition, the soil crusts, with a thickness of 12.5 mm and a calcium carbonate (CaCO3) content of 0.57%, remained intact on the surface of man-made mounds after being exposed to a 30 m/s wind for 2 min. For the sandy land, the soil bearing capacity could reach its maximum of 459.9 kPa (as measured with a 6 mm-diameter handheld penetrometer) within three days, and the depth of wind erosion was approximately zero after 30 days of exposure to the local weather conditions. Furthermore, the biocementation method showed its ecological compatibility at the optimal dosage. Scanning electron microscopy (SEM) tests with energy dispersive X-ray (EDX) confirmed the bridge effect of CaCO3 crystals. Longer-term durability of MICP treatment was evaluated, and the results showed that soil bearing capacity and wind erosion resistance of the sandy land was significantly improved over 180 days. These findings suggest that MICP is a promising candidate to protect desert soils from wind erosion.